Fabrication of Magnetically Stirrable Anisotropic Microparticles via the Microfluidic Method. (7th May 2018) - Xia, Ming; Kim, Kyung Hak; Park, Bumkyo; Yu, Taekyung; Park, Bum Jun
Abstract: A one‐step strategy to fabricate magnetically stirrable microparticles with geometric/chemical anisotropies via a microfluidic technique combined with partial phase separation is presented. Monodisperse oil‐in‐water microemulsions composed of magnetite nanoparticles (MNPs) and two polymers, polystyrene and poly(d, l ‐lactide‐ co ‐glycolide) (PLGA), dissolved in chloroform are generated using the microfluidic method. Upon incubating the microemulsions in pure water at ambient conditions, the solvent contained in the microemulsions is gradually removed and partial phase separation between the two polymers occurs spontaneously. In the meantime, the microemulsion droplets are vertically aligned due to the density difference of the two polymer phases. During the spontaneous phase separation, the MNPs become unstable and the aggregated MNPs segregate downward by gravity to the denser PLGA phase. After complete removal of the solvent, the resulting particles adopt geometric/chemical anisotropies, and they are magnetically rotatable under an external magnetic field. It is demonstrated that the morphology of the anisotropic particles can be controlled readily by adjusting the ratio of the two polymers as well as the concentration of MNPs. It is believed that the developed method based on the partial phase separation and the gravity‐induced segregation of the MNPs enables large‐scale production of magnetically stirrable microparticles. Abstract : A single‐step strategy is developed to fabricate magnetically stirrable particles with geometric and chemical anisotropies via a microfluidic technique combined with partial phase separation. The morphology of the anisotropic particles can be controlled readily by adjusting the ratio of the two polymers as well as the concentration of the magnetic nanoparticles.